FEEDING THE MEDICINAL RASPBERRY PLANT WITH CULTURAL FERTILIZERS (Scientific journal of the Fergana State University, 2025)
Barnaul, Vislukha, Progress, and Malboro varieties of raspberry, one of the berry fruits grown in our country today, have been planted and a high yield of them has been established.